Nicotinamide Adenine Dinucleotide (NAD+) improves lung function in rat lung ex-vivo lung perfusion model. (28th May 2021) - Ehrsam, J P; Arni, S; Chen, J; Rodriguez Cetina Biefer, H; Opitz, I; Inci, I
Abstract: Objective: Ischemia-reperfusion injury compromises short- and long-term outcome after lung transplantation. The scarce existing data on the natural co-enzyme NAD+ suggest an antagonistic effect on hypoxia induced vasoconstriction, removal capacity on reactive oxygen species, and anti-inflammatory effects. We therefore investigated the impact of NAD+ on ischemic rat lungs during ex-vivo lung perfusion (EVLP). Methods: Lungs were retrieved from 12 outbred Sprague Dawley male rats and exposed to 14 hours of cold ischemic storage. All lungs were then perfused in a rat EVLP system for 4 hours. Lung grafts were injected after 1, 2 and 3 hours with 2000 uM NAD + (N = 6) or placebo (N = 6) in the perfusate in proximity of the pulmonary artery. EVLP physiology and biochemistry were monitored. Results: During the 4 hours of EVLP, the lung function increased significantly in the NAD+ group when compared to the placebo group. We monitored a higher vascular flow (p = 0.018), a lower mean pulmonary pressure (p = 0.007) and increased oxygenation capacity (p = 0.003). Lung compliance and weight were comparable. Tissue inflammation measured by myeloperoxidase was significantly lower in the NAD+ group (p = 0.015). In the perfusate, we observed in the NAD+ group significantly lower levels of pro-inflammatory interleukin-18 (p = 0.033) and a trend towards high levels of anti-inflammatory interleukin-10 (p = 0.080) and low levels of pro-inflammatory interleukin-12 (p = 0.146). Conclusion: Findings from this preliminary study demonstrated that NAD+ is a promising agent with both anti-inflammatory properties and the ability to improve ischemic lung function. This observation should be validated in a large animal model.